Higher mineralized bone volume is associated with a lower plain X-Ray vascular calcification score in hemodialysis patients - Adragao, Teresa (PLoS One, 2017)
BACKGROUND AND OBJECTIVES: In dialysis patients, there is an increasing evidence that altered bone metabolism is associated with cardiovascular calcifications. The main objective of this study was to analyse, in hemodialysis patients, the relationships between bone turnover, mineralization and volume, evaluated in bone biopsies, with a plain X-ray vascular calcification score. DESIGN, SETTING, PARTICIPANTS AND MEASUREMENTS: In a cross-sectional study, bone biopsies and evaluation of vascular calcifications were performed in fifty hemodialysis patients. Cancellous bone volume, mineralized bone volume, osteoid volume, activation frequency, bone formation rate/bone surface, osteoid thickness and mineralization lag time were determined by histomorphometry. Vascular calcifications were assessed by the simple vascular calcification score (SVCS) in plain X-Ray of pelvis and hands and, for comparison, by the Agatston score in Multi-Slice Computed Tomography (MSCT). RESULTS: SVCS≥3 was present in 20 patients (40%). Low and high bone turnover were present in 54% and 38% of patients, respectively. Low bone volume was present in 20% of patients. In multivariable analysis, higher age (p = 0.015) and longer hemodialysis duration (p = 0.017) were associated with SVCS≥3. Contrary to cancellous bone volume, the addition to this model of mineralized bone volume (OR = 0.863; 95%CI: 0.766, 0.971; p = 0.015), improved the performance of the model. For each increase of 1% in mineralized bone volume there was a 13.7% decrease in the odds of having SVCS≥3 (p = 0.015). An Agatston score>400 was observed in 80% of the patients with a SVCS≥3 versus 4% of patients with a SVCS<3, (p<0.001). CONCLUSION: Higher mineralized bone volume was associated with a lower plain X-ray vascular calcification. This study corroborates the hypothesis of the existence of a link between bone and vessel and reinforces the clinical utility of this simple and inexpensive vascular calcification score in dialysis patients.